Reason for Decreasing Trend of Students' Number in Tribhuvan University - Dhakal, Ghan Shyam (Adhyayan Journal, 2025)
This article is intended to find out reason behind falling students' number in Tribhuvan University through study of business model elements adopted by the university. Survey method through questionnaire and Grey- TOPSIS method for mathematical interpretation is used in this research. Grey-TOPSIS method is a mathematical interpretation tool that can be used to analyze raw data. The limitation of this research is that it is based on students of Tribhuvan University rather than other universities. Though the output of result may vary from one student to another, sample population taken into consideration in research have shown that the reason behind loss of students is due to lack of proper identification of key partners by the university. Besides key partners, the university should keep their major focus on revenue streams, cost structure and value proposition respectively. The probability of increasing number of students is not far away if the university prioritize their activities as per these findings.